2005
DOI: 10.1029/2004ja010500
|View full text |Cite
|
Sign up to set email alerts
|

Kp forecast models

Abstract: [1] Magnetically active times, e.g., Kp > 5, are notoriously difficult to predict, precisely the times when such predictions are crucial to the space weather users. Taking advantage of the routinely available solar wind measurements at Langrangian point (L1) and nowcast Kps, Kp forecast models based on neural networks were developed with the focus on improving the forecast for active times. To satisfy different needs and operational constraints, three models were developed: (1) a model that inputs nowcast Kp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(186 citation statements)
references
References 32 publications
(60 reference statements)
7
176
2
1
Order By: Relevance
“…Auroral activity Level The index is predicted every 15 min by the use of the Wing Kp Predicted Activity Index model (Wing et al 2005), which takes into account the most recent estimated Kp values and the response of solar wind parameters (neural network algorithm).…”
Section: Kpmentioning
confidence: 99%
See 1 more Smart Citation
“…Auroral activity Level The index is predicted every 15 min by the use of the Wing Kp Predicted Activity Index model (Wing et al 2005), which takes into account the most recent estimated Kp values and the response of solar wind parameters (neural network algorithm).…”
Section: Kpmentioning
confidence: 99%
“…When the input data come from a satellite located approximately 1 h upstream in the solar wind, the resultant predicted Kp forecast is relatively short term (Costello 1997;Wing et al 2005). It gives a 1-or 4-h warning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the solar wind and IMF are the drivers for geomagnetic activity and can be used to predict geomagnetic activity [e.g., Wing et al, 2005;Fung and Shao, 2008;and Bala and Reiff, 2012]. To select a solar wind speed proxy, we examine correlations of solar wind speed with several measures of geomagnetic activity: the auroral electrojet index (AE), Kp, and the polar cap potential (PC).…”
Section: Substitute For Ace Solar Wind Speeds During Outagesmentioning
confidence: 99%
“…For example, the solar wind speed and magnetic field components are used at SWPC as model inputs to predict the Kp index, a measure of global magnetic disturbances [Wing et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The Global D-Region Absorption Product addresses the operational impact of the solar X-ray flux and SEP events on HF radio communication, providing a global map of the highest frequency affected by absorption of 1 dB due to either solar X-ray flux or SEP events or a combination of both, an attenuation bar graph, status messages, and an estimated recovery clock. -Geomagnetic Predictions: The Wing Kp Predicted Geomagnetic Activity Index model (Wing et al 2005) provides 1 h and 4 h predictions of the Kp index. -Satellite Environments Predictions: The Relativistic Electron Forecast Model (REFM) predicts the >2 MeV 24-h electron fluence at geo-synchronous orbit.…”
Section: Introductionmentioning
confidence: 99%